Evidence on the effectiveness of health literacy interventions in the EU: a systematic review - Boudewijn B Visscher; Bas Steunenberg; Monique Heijmans; J. Hofstede; W.L.J.M. Devillé; Iris van der Heide; Jany Rademakers (2018)
In the last decade, the attention for health literacy has increased in the European Union. This is due to three main reasons. First, reviews have shown that inadequate health literacy is associated with worse health outcomes, higher health care use and expenditure. Second, in all European countries the population is aging and the number of chronically ill people is rising. Improving health literacy in this group can offer greater opportunities to take an active part in society, be independent and improve quality of life. Third, since most research on health literacy has been conducted outside Europe and relatively little is known about the development of health literacy interventions and its effects on outcome measures in European countries. The aim of this systematic review was to assess the evidence on the effectiveness of health literacy interventions in the European Union published between 1995 and 2018. Searches have been performed in Medline, PubMed, EMBASE, CINAHL, Cochrane library, PsychINFO, ERIC, Web of Science and SCOPUS for publications on health literacy intervention studies in European Union countries. Studies were included if the research was conducted in one or more Member States of the European Union, the publication described an intervention study, the intervention was aimed at health literacy, the publication described an outcome measure related to health literacy and the publication was written in English, French or German. A total of 23 studies were included. Three types of interventions were identified; aimed at improving health literacy, tailored to different health literacy levels and aimed at improving health outcomes in general that differentiated in effects for people with different health literacy levels. Most interventions identified in the review focus on the functional level of health literacy or numeracy. The strength of evidence from the European health literacy intervention studies was low and there was a huge heterogeneity in study design, measurement tools and outcomes measured. Promising interventions were tailored to the needs of patients, addressing functional, interactive and critical skills and use not difficult animated spoken text. Future research should focus on the development and assessment of such interventions and use stronger designs.